E-Retribusi Pasar Di Pasar Galiran Kabupaten Klungkung Dalam Perspektif Good Governance - Pradhana Yasa, I Gusti Ngurah Putu Ary; Sastra Wijaya, Komang Adi; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2022)
Market E-Retribution in Galiran Market is an effort by the Klungkung Regency Government to prevent fraud in the absorption of market retribution income. The implementation of e-retribution gives hope for the realization of improvements in terms of accountability, transparency, and effectiveness, which are some of the principles of implementing good governance. However, in reality there are problems arises in some of these principles. The purpose of this research is to find out how the market e-retribution in Galiran Market is in the perspective of good governance. The theory used is theory of good governance according to Mardiasmo’s indicators, there are: accountability and transparency, participation, then effectiveness and efficiency. This research uses qualitative methods. The results of research show the market e-retribution Galiran Market has not optimally indicated the implementation of good governance, because indicator of accountability and transparency have not implemented optimally and indicator of participation have not implemented properly.